Engagement and learning in simulation: recommendations of the Simnovate Engaged Learning Domain Group. (24th March 2017) - Choi, Wayne; Dyens, Ollivier; Chan, Teresa; Schijven, Mariles; Lajoie, Susanne; Mancini, Mary E; Dev, Parvati; Fellander-Tsai, Li; Ferland, Mathieu; Kato, Pamela; Lau, James; Montonaro, Michael; et al.
Abstract : Background: Health professions education (HPE) is based on deliberate learning activities and clinical immersion to achieve clinical competence. Simulation is a tool that helps bridge the knowledge-to-action gap through deliberate learning. This paper considers how to optimally engage learners in simulation activities as part of HPE. Methods: The Simnovate Engaged Learning Domain Group undertook 3 teleconferences to survey the current concepts regarding pervasive learning. Specific attention was paid to engagement in the learning process, with respect to fidelity, realism and emotions, and the use of narratives in HPE simulation. Results: This paper found that while many types of simulation exist, the current ways to categorise the types of simulation do not sufficiently describe what a particular simulation will entail. This paper introduces a novel framework to describe simulation by deconstructing a simulation activity into 3 core characteristics (scope, modality and environment). Then, the paper discusses how engagement is at the heart of the learning process, but remained an understudied phenomenon with respect to HPE simulation. Building on the first part, a conceptual framework for engaged learning in HPE simulation was derived, with potential use across all HPE methods. Discussion: The framework considers how the 3 characteristics of simulation interplay with the dimensions of fidelity (physical, conceptual and emotional), and how these can be conveyed by and articulated through beauty (as a proxy for efficiency) as coexisting factors to drive learner engagement. This framework leads to the translation of deliberately taught knowledge, skills and attitudes into clinical competence and subsequent performance.